HUBUNGAN GAYA KEPEMIMPINAN DENGAN KEPUASAN KERJA DI PT X - Oktavia, Serly; Moerkardjono, Sukma Rani (Noetic Psychology, 2015)
Â Abstract. Job satisfaction is a positive feeling about a job that resulting from an evaluation of its characteristics and could effect organization life. Job satisfaction can be influenced by an aspect such as supervision from leader. Supervision is the relationship between leader and follower. There is two styles of leadership when viewed from the interaction between leader and follower, those are transactional and transformational leadership. The aim of this study was to find out the relationship between transactional and transformational leadership with the level of job satisfaction in PT X. The hypotheses of this research were; (1) there was a positive relationship between transactional leadership and job satisfaction and (2) there was a positive relationship between transformational leadership and job satisfaction. The subjects of this research were the employees that are categorized as staff in PT X. Quantitative approach was used using the scale of leadership style and job satisfaction. The data was analyzed by using Pearson Product Moment correlation test. The result of this study showed (1) there is a positive relationship between transactional leadership and the level of job satisfaction; and (2) there is a positive relationship between transformational leadership and the level of job satisfaction. Based on the result of this study, levels of trust also had relationship with leadership style and job satisfaction.Keywords: leadership style, transactional, transformational, job satisfaction